2018
DOI: 10.1177/0363546518759730
|View full text |Cite
|
Sign up to set email alerts
|

Open Latarjet Procedures Produce Better Outcomes in Competitive Athletes Compared With Recreational Athletes: A Clinical Comparative Study of 106 Athletes Aged Under 30 Years

Abstract: The OLP could be considered for primary shoulder stabilization, particularly in competitive athletes, who have high functional demands and great risks of redislocation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
39
0
4

Year Published

2019
2019
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 42 publications
(44 citation statements)
references
References 45 publications
(49 reference statements)
1
39
0
4
Order By: Relevance
“… # References 1, 3, 9-11, 13, 15, 16, 18, 21, 22, 24, 26, 32-36, 38, 42, 43, 46, 50-52, 56, 57, 60, 62, 64, 65, 68, 70-72, 80, 84-86, 93, 95, 97, 101-105, 107, 109-112. …”
mentioning
confidence: 99%
See 1 more Smart Citation
“… # References 1, 3, 9-11, 13, 15, 16, 18, 21, 22, 24, 26, 32-36, 38, 42, 43, 46, 50-52, 56, 57, 60, 62, 64, 65, 68, 70-72, 80, 84-86, 93, 95, 97, 101-105, 107, 109-112. …”
mentioning
confidence: 99%
“… §§ References 10, 13, 21, 26, 32, 40, 43, 46, 50, 52, 62, 64, 71, 80, 85, 95, 97, 103-105, 111, 112. …”
mentioning
confidence: 99%
“…The Rowe score was used most frequently in the studies we reviewed. We found that 22 studies ‡‡ contained the 3 items of stability, motion, and function; 6 studies 56,74,77,79,95,100 used the 4 items of function, stability, pain, and motion; 3 studies 13,16,15 recorded pain, motion, stability, function, and strength; and 1 study 91 included stability, motion, and function. Further, 7 studies 6,25,46,63,64,75,90 provided no information about the version of Rowe score they used.…”
Section: Resultsmentioning
confidence: 99%
“…A total of 7 (11%) studies 18,24,39,42,70,76,101 used a generic health questionnaire in combination with a disease-specific PRO tool, whereas 22 (35%) studies §§ used a visual analog scale to assess pain in combination with a disease-specific and/or generic health questionnaire. Further, 8 (13%) studies 15,22,37,42,72,73,85,86 recorded the results of a sport-specific questionnaire in combination with a disease-specific and/or generic health questionnaire. No studies included in our review used a PRO tool to assess psychosocial factors.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation